Delivery of new terms and concepts in a given department - Plested Alvarez, Maria Cecilia; Campo, Angela María; Quiroz Herrera, Gabriel Angel; Muñoz Torres, Carlos Arturo (Íkala, Revista de Lenguaje y Cultura, 1998)
This article presents a necessary and important preparation phase of the methodology in terminology. This methodological procedure preliminary to the terminological research in the specific area of Somatic Culture, demands processes enrooted in the field of Neology. This addresses first of all, nowadays, the terminologies that are in consolidation.